Using Weekly Group Political Presentations to Enhance the Phonological Learning of Second-Year English Major Students at a University in Vietnam - Andrew, Martin Benedict; Tran, Le Hong (Universitas Negeri Makassar, 2019)
Studies about the learning value of group presentations in ESL and EFL have become increasingly common, particularly in relation to spoken fluency. However, few studies have explored their impact on students’ intelligible pronunciation. In a Vietnamese context, recent changes in teaching and learning strategies set by the government have shifted attention to students’ ability to communicate effectively in today’s increasingly globalized environment. This inevitably turns the spotlight on pronunciation, an aspect of EFL long ignored in Vietnam. Qualitatively describing a case where group presentations were a key mode of teaching, learning and assessment for 17 second-year students majoring in English for Political Discipline at the Institute of International Studies in Hanoi over the course of one semester, this study suggests that monitored and transcribed group presentations may be one rational answer. The study investigates the impacts on participants’ pronunciation of sounds and word stress and considers their attitude towards this method. The results reveal that students acknowledged the benefits of group presentations and experienced improvements in pronunciation, confidence and range of political vocabulary. These changes were diverse depending on each participant’s attitude. The article concludes with reflective evaluations of the lessons and explores the pedagogical implications for future projects on implementing research into presentations among Vietnamese students of foreign languages.